Manajemen Dakwah Pesantren Berbasis Daring: Studi pada Kanal Youtube AlamienTV - Moh. Lukman Hakim (Fakultas Ushuluddin, Adab dan Dakwah, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2020)
Rapid development in the area of information and communication technology has attracted most organization to move into the digital world. In the world of education, not only contemporary schools but also Islamic boarding schools (pesantren) have also begun to migrate to the digital realm. One of the aspects of Islamic boarding schools that has begun to penetrate the online world is the process of preaching. In the past, Islamic boarding schools was only known as institutions to study classical books and religious laws internally, but nowadays many Islamic boarding schools have started to develop media to expand the reach of their da'wah, one of which is the Al-Amien Prenduan Islamic Boarding School with its Youtube channel called AlamienTV. This study aims to find out how Al-Amien Prenduan uses AlamienTV as an online-based da'wah tool. Using a qualitative approach with framing analysis, this article finds that AlamienTV is a place for Al-Amien Prenduan to preach about religion, education, and culture. Keywords: Management, Da’wah, Online, Boarding School